Pembinaan Sikap Positif Berbahasa Indonesia Anak dalam Ranah Media Sosial Bagi Orang Tua Siswa - Anita Rachman; Siti Sumarsilah; Susandi Susandi (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
e purpose of the service activities carried out by Lecturer of the Indonesian Language and Literature Education Study Program, IKIP Budi Utomo, is to provide positive development for children's Indonesian language attitudes in the realm of social media for parents of students at Syuhada Kindergarten Malang. This service activity is expected to provide understanding to parents to give a positive attitude in the use of the Indonesian language. The method used in this activity is to give permission to the principal as well as discuss the problems experienced by partners. The activities were then carried out for three days. The results of this activity, namely providing an understanding to parents about the positive attitude of speaking Indonesian children in the realm of social media for parents. Provide an understanding that a positive attitude will shape character for children.